Kemampuan Membaca Puisi pada Siswa Kelas VIII di SMP Negeri 1 Batanghari Kabupaten Lampung Timur - Hapsari, Winie Setia Prilapnita (Indonesian Research Journal on Education, 2022)
This research aims (1) want to know the ability to read poetry in students, (2) want to describe thepercentage of students' poetry reading ability, (3) want to know the factor that affect students reading ability. The subjects in this study were eight in junior high school 1 Batanghari, Lampung Timur. This research was conducted with a qualitative descriptive method. The data was collected by using the action test technique, namely the poetry reading test according to predetermined indicators. The research dataanalysis was carried out qualitatively. From the data analysis that has been done, it can be concluded that the student class VIII ability to comprehend poetry is low with score of 50%. This is caused by several factors, namely internal factors including 1) interests, 2) pleasures and 3) habist, while the influence of external factors include 1) library utilization, 2) reading opportunities, and 3) maximum value.